Exploring the dynamic diffusion of low‐carbon technology research and development among enterprises: Based on an evolutionary game model with a two‐level heterogeneous social network - Lou, Wen‐qian; Wu, Bin; Chen, Feng; Zhu, Bo‐wen (Managerial and decision economics, 2024)
This study builds an evolutionary game model based on a social network composed of two sub‐networks with different typologies, which respectively depict the connections of enterprises and consumers. Enterprises engage in evolutionary games to determine whether to invest in low‐carbon technology (LCT) research and development (R&D), while consumers select products based on the contrast effect. Our results show that carbon taxation and subsidies can increase the diffusion of LCT R&D, but their marginal effectiveness decreases. Lowering the loan interest rate of enterprises with better green credit can promote LCT R&D diffusion, while excessively lowering the threshold will inhibit that.